Discovery of novel drug candidates for inhibition of soluble epoxide hydrolase of arachidonic acid cascade pathway implicated in atherosclerosis. (June 2018) - Gurung, Arun Bahadur; Mayengbam, Bishwarjit; Bhattacharjee, Atanu
Graphical abstract: Highlights: ZINC23099069 shows high binding affinity with sEH. It exhibits two hydrogen bonds (Tyr383 and His420) and hydrophobic interactions. It possesses acceptable drug-like properties. Its binding caused decreased fluctuations in sEH. Its binding is driven predominantly by electrostatic energy. Abstract: Soluble epoxide hydrolase (sEH), a key enzyme belonging to cytochrome P450 pathway of arachidonic acid cascade is a novel therapeutic drug target against atherosclerosis. The enzyme breaks down epoxyeicosatrienoic acid (EETs) to dihydroxy-eicosatrienoic acids (DHETs) and reduces beneficial cardiovascular properties of EETs. Thus, the present work is aimed at identification of potential leads as sEH inhibitors which will sustain the beneficial properties of EETs in vivo. PubChem and ZINC databases were screened for drug-like compounds based on Lipinski's rule of five and in silico toxicity filters. The binding potential of the drug-like compounds with sEH was explored using molecular docking. The top ranked lead (ZINC23099069) showed higher GOLD score compared with that of the control, 12-(3-adamantan-1-yl-ureido)-dodecanoic acid butyl ester (AUDA-BE) and displayed two hydrogen bonds with Tyr383 and His420 and eleven residues involved in hydrophobic interactions with sEH. The apo_sEH and sEH_ZINC23099069 complex showed stable trajectories during 20 ns time scale of molecular dynamics (MD) simulation. Molecular Mechanics Poisson-Boltzmann Surface Area (MM/PBSA) binding free energy analysis showed that electrostatic energy is the driving energy component for interaction of the lead with sEH. These results demonstrate ZINC23099069 to be a promising drug candidate as sEH inhibitor against atherosclerosis instead of the present urea-based inhibitors.